INVESTIGATION OF COPPER-ALUMINUM OXIDE METAL MATRIX COMPOSITES: EFFECT OF PARTICLE SIZE AND VOLUME FRACTION ON MECHANICAL PROPERTIES - Tiba jamal ahmed (Journals Park Publishing, 2025)
This research study the synthesis and characterization of copper-aluminum oxide (Cu-Al2O) metal matrix composites made through powder metallurgy. The aim of research is to study two variables: (1) Al2O3 particle size (nano sized = < 50 nm; micro sized = 5-10 μm); and (2) volume fractions (2.5%, 5%, 7.5%, 10%), and on augmentation of mechanical properties. Bulk copper powders (>99.9% copper purity) and aluminum oxide particles, were mixed together, cold pressed at pressures at or above 100 MPa - 400 MPa, and sintered in hydrogen at 850°C. Microstructural characterization was completed by using scanning electron microscopy (SEM) and X-ray diffraction (XRD). Mechanical characterization including hardness (Vickers), compressive strength, and density was determined. Many of the results indicate that nano sized Al2O3 produced superior mechanical properties than the micro sized Al2O3. Best composition was Cu-7.5 vol% nano sized Al2O3 produced 145 HV hardness (178% increase) and 420 MPa in compressive strength and 89% conductivity compared to pure copper. Microstructural examination indicated that nano fortified samples had good particle distribution while the micro samples had particle clumping. The proposed mechanisms for the enhancement in mechanical properties were load transfer, grain refinement, and thermal mismatch strengthening. This paper demonstrates the possibilities of Cu-Al2O3 designed composites as thermal and electrical management materials.
Keywords: Copper matrix composites, Aluminum oxide, Powder metallurgy, Mechanical properties, Particle size effect.